The test research fenolsufonptaleina renal function - Velásquez, Manuel A. (1918)
We continue the study of indirect methods of assessment of renal function, based on the introduction into the body of substances that are eliminated by the kidney, either at the level of the glomerulus and a secretory process of renal cell methods will deal of fenolsulfonptaleína, substance introduced by Rowntree and GEPAGHTY to study kidney function, and has the advantage of being innocuous and unalterable part, and be totally eliminated by the kidney, revealing minimal alterations of this body to another.